Weight Stigma in Physical and Occupational Therapy: A Scoping Review - Jason Brumitt; Katherine Turner (Obesities, 2025)
Background: Weight stigma describes the negative attitudes held toward people with obesity. Weight bias stereotypes have been previously reported in physicians, physician assistants, nurses, registered dieticians, psychologists, and students enrolled in healthcare professional education programs. Physical and occupational therapists (PTs and OTs) are healthcare providers who evaluate and treat individuals across their lifespan. A PT or an OT who harbors weight bias may create an environment where the patient may fail to optimize their rehabilitation recovery. The first purpose of this scoping review was to identify the prevalence of weight bias in PT and OT clinicians and students. The second purpose was to evaluate the effectiveness of interventions at reducing weight bias in these populations. Methods: The CINAHL, PubMed, and Google Scholar databases were searched, and 15 articles met the inclusion criteria. Results: In each study, PT and/or OT clinicians and/or students demonstrated weight bias. A minimum of approximately twenty percent of surveyed participants had weight bias, with one study reporting over eighty percent of subjects expressing negative attitudes. Three of the studies reported mixed results (i.e., improvement or worsening) regarding weight bias scores after intervention. Conclusions: PT and OT clinicians and students demonstrate weight bias similar to other healthcare professionals. Future research is warranted to identify educational interventions that reduce bias within these populations.